Catalytic dye degradation by novel phytofabricated silver/zinc oxide composites - Bloch, Khalida; Mohammed, Shahansha M.; Karmakar, Srikanta; Shukla, Satyajit; Asok, Adersh; Banerjee, Kaushik; Patil-Sawant, Reshma; Mohd Kaus, Noor Haida; Thongmee, Sirikanjana; Ghosh, Sougata (Frontiers in Chemistry, 2022)
Phytofabrication of the nanoparticles with exotic shape and size is an attractive area where nanostructures with noteworthy physicochemical and optoelectronic properties that can be significantly employed for photocatalytic dye degradation. In this study a medicinal plant, Plumbago auriculata leaf extract (PALE) was used to synthesize zinc oxide particles (ZnOPs) and silver mixed zinc oxide particles (ZnOAg1Ps, ZnOAg10Ps, ZnO10Ag1Ps) by varying the concentration of the metal precursor salts, i.e. zinc acetate and silver nitrate. The PALE showed significantly high concentrations of polyphenols, flavonoids, reducing sugar, starch, citric acid and plumbagin up to 314.3 ± 0.33, 960.0 ± 2.88, 121.3 ± 4.60, 150.3 ± 3.17, 109.4 ± 2.36, and 260.4 ± 8.90 μg/ml, respectively which might play an important role for green synthesis and capping of the phytogenic nanoparticles. The resulting particles were polydispersed which were mostly irregular, spherical, hexagonal and rod like in shape. The pristine ZnOPs exhibited a UV absorption band at 352 nm which shifted around 370 in the Ag mixed ZnOPs with concomitant appearance of peaks at 560 and 635 nm in ZnO10Ag1Ps and ZnOAg1Ps, respectively. The majority of the ZnOPs, ZnOAg1Ps, ZnOAg10Ps, and ZnO10Ag1Ps were 407, 98, 231, and 90 nm in size, respectively. Energy dispersive spectra confirmed the elemental composition of the particles while Fourier transform infrared spectra showed the involvement of the peptide and methyl functional groups in the synthesis and capping of the particles. The composites exhibited superior photocatalytic degradation of methylene blue dye, maximum being 95.7% by the ZnOAg10Ps with a rate constant of 0.0463 s−1 following a first order kinetic model. The present result clearly highlights that Ag mixed ZnOPs synthesized using Plumbago auriculata leaf extract (PALE) can play a critical role in removal of hazardous dyes from effluents of textile and dye industries. Further expanding the application of these phytofabricated composites will promote a significant complementary and alternative strategy for treating refractory pollutants from wastewater.